A Retrospective Investigation of Determining the Factors of Dental Implant Survival Rate - Syed Ali Danish Kazmi, Abdulfattah Omar, Hina Manzoor, Tahsinul Haque, Atifa Rashid, Rubina Kousar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Dentists have developed as both a novel potential treatment for the majority of the patients, and they are projected to play aa significant part in oral rehabilitation in future. The latest research was carried out to evaluate several parameters influencing the chance of survival of dental work. Methods: The current investigation was carried out in Services Hospital, Lahore. This study includes 5300 individuals who had dental implants implanted between June 2020 and May 2021. Individuals with hormonal imbalances, chronic infectious illnesses, immunosuppressive medication, pregnant women, drug and alcohol abusers, and suffering from chronic periodontal disorders have also been excluded. Name, age, gender, length of implant, diameter of implant, placement of implant, and biomechanical properties were among the parameters reported. Results: There were 2900 men and 2500 women among 5400 individuals. Highest implantation losses (56) were observed in patients above the age of 59 (males – 560, females – 740). There were 21 unsuccessful implantations in the 41-year-old age category (males 760, women 560). There were 46 unsuccessful implants in the age category 40–61 years (males – 1600, women – 1100). The change remained not statistically substantial (P = 0.22). Implant with a length of more than 12.6 mm (44/720) failed the most, followed by implant with a length of 11 mm (23/1670) and 11–11.6 mm (63/2870). The increase was statistical implication (P 0.06). Fasteners with just a diameter of 4.77 mm (17/1640) and implantation with a length of 5.77–3.6 mm (53/2700) failed the most (33/1050). Conclusion: The existence rate of prostheses is resolute by limitations just like age, entrenched length, diameter, bone quality, also implanted location. Researchers discovered that implants more than 12.6 mm in height and 4.76 mm in diameter, put in the mandibular posterior area of Type III bones, had the highest failure rate. Keywords: Dental Implant Survival Rate, potential treatment.